Inter-Enterprise Networking in Developing Regions: An International Stability Perspective. Issue 29 (2016) - Limani, Ylber; Stapleton, Larry
Abstract: Regardless of all possible circumstances, there is sufficient evidence that shows inter-enterprise networking information automation systems are a major force in globalisation trends, They can contribute to widening or narrowing the digital divide between more developed and less developed economies, contributing to long term instability pressures where the conditions are not in place which encourage and support local enterprise networks to adopt the technology. This working paper presents insights into the e-readiness of a post-conflict, transition region in the western Balkans, and provides some explorative research concerned with the dimensions and factors affecting business network in the region.